2008
DOI: 10.1210/me.2008-0067
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Deficiency Mediates Hyperphagic Obesity of Sim1 Haploinsufficient Mice

Abstract: Single-minded 1 (Sim1) encodes a transcription factor essential for formation of the hypothalamic paraventricular nucleus (PVN). Sim1 haploinsufficiency is associated with hyperphagic obesity and increased linear growth in humans and mice, similar to the phenotype of melanocortin 4 receptor (Mc4r) mutations. PVN neurons in Sim1(+/-) mice are hyporesponsive to the melanocortin agonist melanotan II. PVN neuropeptides oxytocin (Oxt), TRH and CRH inhibit feeding when administered centrally. Consequently, we hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
231
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(244 citation statements)
references
References 58 publications
10
231
0
1
Order By: Relevance
“…Importantly, oxytocin has also been convincingly linked with protection from obesity [17][18][19][20][21][22][23]. While the nonapeptide oxytocin is historically recognized for its role in parturition [24] and lactation [25] it has gained more recent attention for its apparent effects on prosocial behavior [26,27] and therapeutic potential in the treatment of autism spectrum disorder (ASD) [26,27], schizophrenia [26,28] and obesity [17][18][19][20][21][22][23]. A large number of ongoing investigations in humans list oxytocin as the focus in studies on caloric intake, gastric emptying, or obesity, as displayed in the ClinicalTrials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, oxytocin has also been convincingly linked with protection from obesity [17][18][19][20][21][22][23]. While the nonapeptide oxytocin is historically recognized for its role in parturition [24] and lactation [25] it has gained more recent attention for its apparent effects on prosocial behavior [26,27] and therapeutic potential in the treatment of autism spectrum disorder (ASD) [26,27], schizophrenia [26,28] and obesity [17][18][19][20][21][22][23]. A large number of ongoing investigations in humans list oxytocin as the focus in studies on caloric intake, gastric emptying, or obesity, as displayed in the ClinicalTrials.…”
Section: Introductionmentioning
confidence: 99%
“…gov registry, National Institutes of Health. Specifically, studies show oxytocin has roles in reducing food intake and body weight in dietinduced obesity [17,19,[21][22][23] in genetically obese rodent models [18,20,21], highlighting potential downstream CNS and peripheral mechanisms. It was also shown that intranasal administration of oxytocin in humans lowers caloric intake and has beneficial metabolic effects, resulting in a shift from carbohydrate to fat utilization and improved insulin sensitivity [29].…”
Section: Introductionmentioning
confidence: 99%
“…It has so far been studied mainly with a focus on hyperphagia and obesity, with an effect demonstrated by mice haploinsufficient for the SIM1 gene (Xi et al, 2012). It has been shown that SIM1 is important for oxytocin expression in the PVN, with a near 80% reduction in haploinsufficient mice (Kublaoui et al, 2008). In the PVN and SON, SIM1 is co-expressed with the transcription factor aryl hydrocarbon receptor nuclear translocator 2 (ARNT2).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many studies have linked changes in brain oxytocin signaling with changes in eating behavior: (1) hypothalamic oxytocin mRNA expression is reduced with fasting and is restored upon refeeding; (2) eating activated oxytocin neurons in rats; and (3) reduction of oxytocin mRNA and protein in the paraventricular nucleus led mice to develop obesity, which can be rescued by oxytocin treatment [345,346].…”
Section: Oxytocinmentioning
confidence: 99%
“…More recently, Blevins and colleagues [385,386] confirmed this and also showed that reductions in hindbrain oxytocin signaling reduce the satiating potency of CCK in rats. Leptin also seems to affect this oxytocin signaling: (1) leptin activated paraventricular nucleus oxytocin neurons and increased the expression of oxytocin mRNA in the paraventricular nucleus, probably via melanocortin-dependent mechanisms [345,350,387,388] and (2) third ventricular administration of oxytocin antagonists blunted leptin's anorectic effects and abolished its ability to enhance CCK activation of the NTS [350] as well as reversing the anorectic effect of α-MSH [389].…”
Section: Descending Projections For Satiationmentioning
confidence: 99%